Education Management in Early Childhood Education: Curriculum Governance, Human Resources, Financing, and Quality Development - Herinto Sidik Iriansyah; Saryono Saryono (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
This study aims to identify patterns of findings, research trends, and research gaps in the field of Early Childhood Education (PAUD) management through a Systematic Literature Review (SLR) approach using the PRISMA protocol. A total of 22 articles published in the recent period were analyzed based on four main domains, namely curriculum management, human resource management, financing/finance, and PAUD quality development. The results of the review show that PAUD management research is still dominated by descriptive approaches and local case studies with a focus on learning implementation, curriculum development, and character building. The important findings of this study reveal gaps in curriculum digitization, comprehensive human resource management systems, alternative financing innovations, and the application of data and technology-based quality management. This study recommends future research directions that focus on the development of digital and inclusive curriculum models, sustainable human resource management, collaborative financing systems, and the development of technology-based Internal Quality Assurance Systems (SPMI). These findings are expected to enrich the literature on PAUD management and serve as a reference for the development of more innovative and sustainable PAUD institutional management policies and practices.